Microplastic interaction with Fe-P coupling pathways induced cadmium immobilization in tropical agricultural soils - Ying Yang; Chaoxian Wei; Pan Pan; Bigui Lin; Zhengfu Yue; Yukun Zou; Beibei Liu (Environmental Pollution, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Aging enhances the ecological toxicity of polyethylene microplastics to marine medaka larvae (Oryzias melastigma) - Shaobai Wen; Jin Liu; Bigui Lin; Na Li; Xiaoping Diao (Journal of Environmental Management, 2026)

Coeffects of iron oxides and phosphorus fractions on soil organic carbon stabilization in rubber-based tropical agroforests - Liping Wang; Chaoxian Wei; Bigui Lin; Xiwang Ke; Qinfen Li; Beibei Liu; Yukun Zou (Journal of Soils and Sediments, 2026)

From biodegradation to biohazard: Polylactic acid microplastics induced rice growth inhibition in agroecosystems - Bigui Lin; Qingfang Fan; Fang Liu; Luya Wang; Chaoxian Wei; Beibei Liu; Juan Zhao; Linzi Zuo; Yi Xie (Journal of Hazardous Materials, 2025)

Observation of Near-Inertial Oscillation in an Anticyclonic Eddy in the Northern South China Sea - Botao Xie; Tao Liu; Bigui Huang; Chujin Liang; Feilong Lin (Journal of Marine Science and Engineering, 2025)
Anticyclonic mesoscale eddies are known to trap and modulate near-inertial kinetic energy (NIKE); however, the spatial distribution of NIKE within the eddy core and periphery, as well as the mechanisms driving its energy cascade to smaller scales, remains inadequately understood. This study analyzed the evolution of NIKE in anticyclonic eddies using satellite altimetry and field observations from four mooring arrays. By extracting near-inertial oscillations (NIOs) and subharmonic wave kinetic energy across mooring stations during the same period, we characterized the spatial structure of NIKE within the eddy field. The results revealed that NIKE was concentrated in the eddy core, where strong NIOs (peak velocity ~0.23 m/s) persisted for ~7 days, with energy primarily distributed at depths of 200–400 m and propagating inward from the periphery. Subharmonic waves fD1 generated by interactions between NIOs and diurnal tides highlighted the role of the vertical nonlinear term in energy transfer. A further analysis indicated that under vorticity confinement, NIKE accumulated in the core of the eddy and dissipated through shear instability and nonlinear wave interactions. The migrating anticyclonic eddy thus acted as a localized energy source, driving mixing and energy dissipation in the ocean interior.

Differences in the uptake and translocation of differentially charged microplastics by the taproot and lateral root of mangroves - Yichun Lin; Luya Wang; Bigui Lin; Beibei Liu; Tingting Guan; Shuai Guo; Qinfen Li; Chaoxian Wei (Science of The Total Environment, 2024)

Identification and health risk evaluation of soil contaminated by polycyclic aromatic hydrocarbons at shale gas extraction sites based on positive matrix factorization - Zhilei Liu; Tong Zheng; Qiyu Chen; Xichao Chen; Yi Xie; Yuyu Wang; Mingzhong Ren; Zhi-qiang Gao; Bigui Lin; Xidan Feng (Chemosphere, 2024)

Health assessment based on exposure to microplastics in tropical agricultural soil - Bigui Lin; Luya Wang; Qiyu Chen; Zhilei Liu; Beibei Liu; Shaobai Wen; Fang Liu; Xichao Chen; Zongyao Zhang; Lin Wu; Chaoxian Wei (Journal of Hazardous Materials, 2024)

The role of pores in micro-zone distribution of Cd in a tropical paddy soil: Results from X-ray computed tomography combined energy dispersive spectroscopy analysis - Chaoxian Wei; Bigui Lin; Beibei Liu; Zhenli He; Qinfen Li (Journal of Hazardous Materials, 2023)

An unrecognized entry pathway of submicrometre plastics into crop root: The split of hole in protective layer - Luya Wang; Beibei Liu; Wen Zhang; Qinfen Li; Bigui Lin; Chaoxian Wei (Journal of Hazardous Materials, 2023)

Response of cadmium adsorption to three-year different agronomic managements in tropical soil: The role of P fractions and Fe oxides - Beibei Liu; Chaoxian Wei; Dengxiu Wei; Miao Chen; Wei Li; Pan Pan; Bigui Lin; Lin Wu; Qinfen Li; Zhenli He (Agriculture, Ecosystems & Environment, 2023)

Phosphorus fractions and iron oxides responsible for the variations in the Cd retention capacity in tropical soil aggregates under different cropping patterns - Dengxiu Wei; Chaoxian Wei; Pan Pan; Bigui Lin; Lin Wu; Beibei Liu; Zhenli He (Journal of Hazardous Materials, 2023)

Polycyclic aromatic hydrocarbons (PAHs) in multi-phases from the drinking water source area of the Pearl River Delta (PRD) in South China: Distribution, source apportionment, and risk assessment - Yunjiang Yu; Ziling Yu; Zhengdong Wang; Bigui Lin; Liangzhong Li; Xichao Chen; Xiaohui Zhu; Mingdeng Xiang; Ruixue Ma (Environmental Science and Pollution Research, 2018)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)